Bleeding Complications in Patients with Hematologic Malignancies - Franchini, Massimo; Frattini, Francesco; Crestani, Silvia; Bonfanti, Carlo (Seminars in Thrombosis and Hemostasis, 2013)
Abnormalities of hemostasis are frequently encountered in patients with hematologic malignancies leading to both hemorrhagic and thrombotic adverse events. The prompt recognition and management of such complications, which have a negative impact on the morbidity and mortality of these patients, represents a major challenge for hematologists. This review describes the most important changes of hemostasis associated with hemorrhage in hematologic malignancies with particular emphasis on their contributory etiologic factors, complex pathogenic mechanisms, clinical manifestations, and therapeutic strategies. In particular, platelet and acquired coagulation abnormalities, bleeding complications in acute leukemia, and hematopoietic stem cell transplantation are discussed.
Keywords: bleeding; leukemia; hematologic malignancies; therapy